2018
DOI: 10.1002/asi.24079
|View full text |Cite
|
Sign up to set email alerts
|

Author‐based analysis of conference versus journal publication in computer science

Abstract: Conference publications in computer science (CS) have attracted scholarly attention due to their unique status as a main research outlet, unlike other science fields where journals are dominantly used for communicating research findings. One frequent research question has been how different conference and journal publications are, considering an article as a unit of analysis. This study takes an author‐based approach to analyze the publishing patterns of 517,763 scholars who have ever published both in CS conf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…In many engineering disciplines and in computer science, publishing in conference proceedings is almost as important as publishing in journals 34 , 35 . This assertion is supported by a typically high valuation of conference contributions in researcher evaluations.…”
Section: Engineering and Computer Sciencementioning
confidence: 99%
“…In many engineering disciplines and in computer science, publishing in conference proceedings is almost as important as publishing in journals 34 , 35 . This assertion is supported by a typically high valuation of conference contributions in researcher evaluations.…”
Section: Engineering and Computer Sciencementioning
confidence: 99%
“…Franceschet concluded by recommending publishing fewer more mature works in journals compared to incremental works in conferences. Although reporting similar observations, Kim (2019) argues that fields outside computer science need to acknowledge the publication patterns within computer science. In a study of nearly 50,000 conference papers, Lee (2019) found that impact was linked to conference longevity, proceedings with few papers, low acceptance rates, broad scope, papers by authors from different countries, and papers presented during the months January through June and August.…”
Section: Journal Versus Conference Dichotomymentioning
confidence: 90%
“…However, results of this study confirm that characteristics of all authors who were more experienced and established than first authors tend to determine the research impact of their conference papers. The marginal predictive effect of less experienced first authors seems to link to the disciplinary culture of computer science and information science that young researchers tend to publish their first papers at conferences (Kim, 2019).…”
Section: Conclusion and Discussionmentioning
confidence: 99%